Animal travellers - Flegg, Dr. Jim (Belitha Press London, 1990)
This series of thematic photographic information books shows aspects of animal behaviour using a wide range of wildlife from the familiar to the exotic as examples. This book describes animals as highly organized and often accomplished travellers.